(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2020)
The research focuses on the development of multiparticulate delivery system for acid-labile Lansoprazole to prevent its degradation in the acidic environment of the stomach and enhance its bioavailability via intestinal absorption. This problem can be solved by enteric coating. In this project, cellulose acetate phthalate a polymer usually utilized for gastrointestinal film coating of tablets, was used to prepare enteric microspheres of lansoprazole with solvent evaporation technique in various formulations such as F1, F2, F3, F4, F5 with drug: polymer ratios of 1:1, 1:2, 1:3, 1:4, 1:5 respectively. FTIR study indicated compatibility between drug and polymer. Increase in concentration of polymer increased spheriocity and mean diameter of the microspheres. The drug entrapment efficiency was in the range of 72.23% to 88.64%. SEM revealed that microspheres were found spherical and porous. In-vitro study proves that drug release slowly increases as the pH of the medium increased and prevents degradation of drug in acidic pH. In-vitro drug release was found to be 92.80%, 94.55%, 92.72%, 96.34%, 98.65% in all 5 formulations. All 5 formulations showed gastric resistance around 80-90%. So it is concluded that the developed enteric coated microspheres of Lansoprazole prevented drug release in the stomach which would lead to significant improvement in its bioavailability through enhanced intestinal absorption.